Exploring the impact of a conspicuous identity on college students’ campus loans: Evidence from China - Zhang, Qi; Zhang, Mingyang; Cheng, Zhiqiang; Zhao, Yiling (Frontiers in Psychology, 2022)
An increasing number of college students have taken out campus loans. This trend has had a negative impact on their learning and development. Using survey data about Chinese college students, this study explores the influence of a conspicuous identity and conformity on campus loan behavior and usage intention. Identify economics posits that identity is a key factor affecting individual behavior and decision-making. Differentiated identify is linked to differentiated social groups and constituted through specific value orientations, social norms and codes of conduct. This study shows that college students with a conspicuous identity are more likely to take out campus loans and more willing to take out such loans in the following year. The discussion on heterogeneity shows that a conspicuous identity has significantly positive effects on campus loan behavior for students in groups with higher consumption and grade, while conformity has significantly positive effects on campus loan behavior when students are in lower-grade groups. Compared with students who have never used campus loans, students who have taken out are more willing to take them out again in the future. Finally, avoidance strategies of campus loan debt are provided from two perspectives, namely, identity construction and the classification of education.